Meteorological parameters and water balance components of Priyadarshini Lake at the Schirmacher Oasis, East Antarctica - Dhote, Pankaj R.; Thakur, Praveen K.; Shevnina, Elena; Kaushik, Suvrat; Verma, Atul; Ray, Yogesh; Aggarwal, S.P. (Polar Science, 2021)
The meteorological parameters and water balance components of Priyadarshini Lake at Schirmacher Oasis, East Antarctica, were studied using meteorological data procured from the India Meteorological Department (IMD) weather station, Maitri and field observations in summer seasons of 2017–2018 and 2018–2019. Meteorological data was analysed (daily temporal and diurnal variation) for 2018, and the water balance components were estimated for January–February of 2018. The present work revealed the status of meteorological parameters (air temperature, relative humidity, wind speed, and snowfall) at Schirmacher Oasis compared to long-term historical trends at the east and west regions of Antarctica. As Priyadarshini Lake is non-endorheic, it transferred freshwater to the sea at the rate of ∼335 × 103 m3/month during summer season of 2018. The water consumption by Maitri station (term W) is very minimal compared to other terms and does not play a substantial role in the lake's water balance. The limited availability of topographic and historical hydro-meteorological data limits the application of physically based hydrological models to simulate snow melt surface runoff at the inflow and assess the impact of climate change on hydrological regimes of the lake. Thus, long term monitoring of the lake with a permanent gauging network for inflows and outflow will pronounce our understanding and enable the option to assess linkage with changing climate. journal article